Subsurface investigation for pre-foundation study utilizing integrated geophysical and geotechnical methods, UNILORIN campus - Gabriel Efomeh Omolaiye; Abdulhameed Kayode Oniyangi; Taofeeq Ayinde ISSA; Sodiq Bamidele Adam (Discover Geoscience)
Abstract This study involves subsurface investigation of a proposed site within senior staff quarters at the University of Ilorin campus utilizing the electrical resistivity technique, magnetic method and geotechnical analysis for the pre-foundation study. The land magnetic survey was acquired at 20 m spacing along seven traverses with the use of Geometrics G857 Proton Precession Magnetometer revealing the presence of concealed basement contact separating the biotite schist in the north from granite gneiss in the south. The Schlumberger configuration was used for the 1-D vertical electrical sounding (VES) technique, with the current electrode spacing (AB/2) varied between 1 and 100 m, which revealed three to four geo-electric layers which include lateritic/topsoil (93-3053Ωm, 0.3–2.5 m), clayey-sand (127-639Ωm, 1–13.2 m), weathered basement/sandy-clay (55-767Ωm, 3.6–33.3 m), and fresh basement (above 1000Ωm). WINRESIST and Surfer were used for the processing of resistivity data while Microsoft Excel was adopted for ground magnetic processing. However, the geotechnical analysis conducted on undisturbed samples picked at different depths from eight pits dug to a depth of 2.3 m revealed the following: bulk density (1.80 g/cm3-1.99 g/cm3), dry density (1.67 g/cm3-1.86 g/cm3) liquid limits (22.3%-34.1%), plastic limits (12.6%-19.8%), plasticity index (9.7%-14.3%) and cone penetration test (89.8 kN/m2-2110.3 kN/m2 at a depth of 0.1 m to 0.3 m), in which all these geotechnical analysis results classified the soil to be competent in variations and assess soil mechanical behaviour to support structural loads within study area. The integration of geophysical and geotechnical results revealed high topsoil resistivity correlates with high bearing capacity and is interpreted as thick and compacted lateritic materials. Highlights: i. Laying of foundation across the contact zone should be avoided and attention must be taken when selecting the foundation's materials. ii. Excavation of the soil to a depth where it is sufficiently consolidated and competent to support any type of construction. iii. The use of a shallow foundation type, such as a raft foundation in areas of lower competence and strip footing in competent areas with large bearing capacities.